Public Awareness on Cancerous Substances - Jusufranic, Jasmin (AVICENA, d.o.o., Sarajevo, 2014)
The public can be defined as a mosaic consisting of various ethnic, religious and other social groups, hence the definition of public includes each individual persona. Public opinion is the voice of such public and is, therefore, considered a worthy element in political and economic discourse. Media can do much in providing education necessary for informing the public about cancerous substances in the environment. The purpose of this study is to inform the public about issues that truly matter instead of following the current trend and focus on the topics and issues of less importance.